Comparative Analysis of Industrial Data Transmission Protocols (IIOT) in Automation Systems - Mandrykov, K.; Sotnik, S. (NURE, 2026)
This work presents a comparative analysis of key data exchange protocols used in modern automation systems. The advantages and disadvantages of protocols such as Modbus TCP, OPC UA, and MQTT were examined and compared in terms of efficiency, security, and implementation complexity within the context of Industry 4.0. The results of the analysis enable the identification of the most suitable communication standards for different levels of the automation pyramid, which can be useful for system integrators and developers. У цій роботі проведено порівняльний аналіз ключових протоколів обміну даними, що використовуються в сучасних системах автоматизації. Було досліджено та зіставлено переваги й недоліки таких протоколів, як Modbus TCP, OPC UA та MQTT, з погляду ефективності, безпеки та складності реалізації в умовах Industry 4.0. Результати аналізу дають змогу виявити найбільш підходящі комунікаційні стандарти для різних рівнів піраміди автоматизації, що може бути корисним для системних інтеграторів та розробників.
Порівняльний аналіз промислових протоколів передачі даних (IIOT) в системах автоматизації
Keywords: Industry 4.0; IIoT; Modbus TCP; OPC UA; MQTT